Functions and Dysfunctions of Electronic Monitoring (KULT_online, 2020)
Tom Daems' book Electronic Monitoring. Tagging Offenders in a Culture of Surveillance  offers a systematic analysis of the development and current application of electronic monitoring (EM). The author examines the functions (both evident and covert) in alphabetical order, questions the goals of the technology and considers it as part of a society in which surveillance practices are omnipresent. Daems offers a compact and critical analysis as well as new thought-provoking impulses.